Modulating Acinetobacter baumannii biofilm development with molecules containing 3, 4, 5-trimethoxy-N, N′, N′-trimethylbenzohydrazide moiety. Issue 10 (15th May 2015) - Sambanthamoorthy, Karthik; Hickman, Mark; Pattabiraman, Nagarajan; Palys, Thomas; Wagar, Eric J.
Graphical abstract: Abstract: In recent years, Acinetobacter baumannii has emerged as a major cause of nosocomial infections, including infections of implanted medical devices. The treatment of infections caused by A. baumannii has been severely hampered due to their frequent resistance to currently available antibiotics, and most importantly the ability of A. baumannii to form biofilms, which plays a significant role in both persistence and antibiotic resistance. The inherent resistance of A. baumannii biofilms to host defenses and antimicrobial agents necessitates the search for novel approaches to deter biofilm formation. Here, we report our findings on nine compounds identified from structure–activity relationship (SAR) studies on an antibiofilm compound LP3134 that was reported earlier by Biofouling 2014, 30, 17. Compounds were evaluated for antibiofilm and anti-adherence activities against A. baumannii . The ability of the compounds to prevent biofilm development on urinary catheters was studied. Growth curve experiments indicated that compounds did not affect the planktonic growth of A. baumannii . All compounds inhibited A. baumannii biofilm development as well as impacting early adhesion on abiotic surfaces. Seven compounds were able to deter biofilm development on silicone catheters. Due to the continued rise of emerging multidrug-resistant A. baumannii, results from this study provide foundation for further development of these molecules to treat A. baumannii infections in wounds and medical devices.